Efecto del programa de incentivos en la recaudación del impuesto al patrimonio predial, Municipalidad Provincial de Cajamarca, 2018 – 2020 - Castillo Cotrina, Karito Lisbeth (2022)
The general objective of this research was to determine the effect of the Incentive Program on the collection of property tax in the Provincial Municipality of Cajamarca in the period 2018-2020, the study population was 399,663 properties in the province of Cajamarca in the year 2021, the sample used was of the occasionally simple probabilistic type, the selected sample was calculated at a confidence level of 95% and an error of 5%, where Sample (n) = 384 inhabitants of the province of Cajamarca in the year 2021, As data collection techniques, the survey and the documentary review were shown, with its questionnaire instruments and data analysis sheet, the reliability of the instruments was prolonged using the Cronbach's Alpha Coefficient, which reached an index of 0.9988 for the questionnaire of variable 1, and 0.994 for the questionnaire of variable 2, finally concluded as follows: The effect of Pro ended Incentive program in the collection of property tax in the Provincial Municipality of Cajamarca in the period 2018-2020, which was the growth in collection for the year 2019 of a total of 38.4%.